Modelling the evolution of new energy vehicle policies (2000–2024): A bibliometric analysis of trends and management implications - Han, Wei; Mohamad Rohieszan, Ramdan; Nor Zafir, Salleh; Nurul Ashykin, Abd Aziz; Nor Liza, Abdullah; Susanto, Perengki (Poznan School of Logistics, 2025)
Background: New Energy Vehicles (NEVs) have become a key solution for addressing the environmental impacts of conventional vehicles, particularly in the context of carbon emissions and energy security. Policymakers globally have introduced various strategies, including financial incentives and infrastructure development, to promote NEV adoption. However, there has been limited comprehensive analysis of the evolution and global trends of NEV policies. This study seeks to bridge this gap by examining the landscape of NEV policy research from 2006 to 2024. Methods:A bibliometric analysis of 499 peer-reviewed studies from Scopus was conducted using the Bibliometrix R- package and Biblioshiny tools. The PRISMA protocol guided the selection process. The analysis examined publication trends, citation networks, collaboration patterns, and the evolution of research themes.